Vintage graphic design type, typography, monograms & decorative design from the late 19th & early 20th centuries - Heller, Steven 1950-; Fili, Louise 1951- (Allworth Press, 2020)
"Any type user and enthusiast will doubtless derive joy from the letters and ornaments in Vintage Graphic Design, gathered from the rare and forgotten sources that authors Steven Heller and Louise Fili have collected over the years. As type gourmets, Heller and Fili savor type in many forms-especially the aesthetically idiosyncratic and the printed artifacts of which historical or retro typefaces are samples. A period of rapid innovation and growth in printing and type technology, the late 1800s and early 1900s saw type foundries in Europe and America burst into wellsprings for bold compositions and arresting typefaces However, this is not a history book; rather, it is a sampler of tasty typographic confections or so-called eye candy. The curated selection here reflects this era's printing material, including stock pictorial cuts, filigree borders, and cartouches galore"--
Keywords: Geschichte 1880-1920; Typografie; Schrift; Grafikdesign; Graphic design (Typography); Printers' ornaments; Type ornaments; Bildband